Modelo estatístico para avaliar o desempenho de um sistema de correção de erro quântico - Franco, Paulo Henrique da Silva (2013)
One of the most used physical properties to implement quantum technology is the polarization of the light. However, since the polarization of the light is fragile, it is essential that a quantum error correction system is used to make quantum information feasible in the polarization of a photon. A method of correction of polarization proposed for isolated photons divides the channel into sub-channels in such a way that only the variation in those sub-channels destroys the information. Therefore, rapid changes must occur in the moment that two optical pulses pass through the sub-channel. This work analyses a statistical model that uses the degree of depolarization of the light as a probability for the sub-channel to undergo minute variations in the time between the passage of two pulses. To model the variations of the parameters of the channel, it is used the probabilistic method of Poisson, applied to rare events. An estimate can be done using numerical methods which measures the degree of polarization of the light to predict how would be the behavior in the practice of the quantum error correction system studied.